Anthecology and reproductive system of Mourera fluviatilis (Podostemaceae): pollination by bees and xenogamy in a predominantly anemophilous and autogamous family? - Sobral-Leite, Marcelo; de Siqueira Filho, José Alves; Erbar, Claudia; Machado, Isabel Cristina (Aquatic botany, 2011)
The Podostemaceae are sessile hydrophytes restricted to habitats with waterfalls and seasonal flow variability. Mourera fluviatilis belongs to the family and has a disjunct distribution in the Amazon and northeastern Brazil. The following hypotheses were tested: (i) both autogamy and anemophily act on the pollination system of M. fluviatilis, and (ii) the highest reproductive success is achieved by cross-pollination. Natural populations were monitored in the rivers Pirangi and Ipojuca, northeastern Brazil. Floral visitors are the polylectic bees Apis mellifera, Trigona spinipes (Apidae), Augochlora sp. and Augochloropsis sp. (Halictidae), though only the latter three are effective pollinators. In experiments on the reproductive system and pollination there was a high percentage of fruit formation (>86%), both in treatment and control plants. Although the index of self-incompatibility is 0.86, there was a significant difference in the number of seeds produced among reproductive system treatments, and xenogamy produced more seeds. There was no significant difference in the number of penetrated ovules between control and manual cross-pollination (xenogamy) treatments, 24h after pollination. However, there were differences among treatments, 48h after pollination, except for the control and xenogamy treatments. The pollen tubes from cross-pollination treatments usually penetrate the micropyle in shorter time and in higher quantity. We found differences among pollination experiments, except for the control and non-emasculated treatments, and between emasculated treatments. In spite of the ambiguity of floral attributes (pedicel, filaments and anthers colors, sweet odor, reduced perianth, absence of nectar, small and dry pollen grains), wind pollination is less important for this species; what predominates instead are first allogamy mediated by bees and second self-pollination at the end of anthesis.
Gesehen am 18.10.2022